Is Self-Regulation Able to Mediate the Effect of Self-Effort on E-Learner Success in the Islamic State University? - Sulistiani, Dwi; Amin, Saiful; Bashith, Abdul (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aim to seek the relationship between self-effort and e-learner success, either directly or through self-regulation. This type of research is quantitative. The research method used is an exploratory survey. Primary data were obtained from questionnaires filled out by 923 Social Science Education students at all State Islamic Universities in Indonesia. 11 State Islamic Universities with a Social Science Education program participated in this research. The direct test uses Ordinary Least Square (OLS), while the indirect effect is tested using the Sobel test. The results of this study can prove that self-effort has a direct and indirect positive influence on e-learner success through self-regulation. Students with high self-effort will be able to improve their self-regulation, impacting their e-learning success. This evidence shows that e-learning requires students' independence to succeed academically. This research provides a theoretical contribution to the development of e-learning theory. Students in online learning success need self-effort and self-regulation because, in online learning, students are required to be more active than in direct learning in class. The author recommends further research to expand other variables that affect the success of e-learning with different models and theories, such as expectation confirmatory theory, technology acceptance model, intention to continue using LMS, course and information quality.